Green Economy: Konsep, Impelentasi dan Peran Kementerian Keuangan - Makmun (Jurnal Ekonomi dan Pembangunan, 2025)
Green economy is relatively a new concept, although in fact it is an advancement of sustainable development concept. Environment based sustainable development is a very popular concept in the west. Indonesia has been implemented this concept for a long time, which is known as “pembangunan berkelanjutan yang berwawasan lingkungan hidup”. In the context of climate change and green economy, Indonesian National Planning Bureau (Bappenas) has launched the Indonesia Climate Change Sectoral Roadmap (ICCSR). The ICCSR elaborates strategies of nine sectors including forestry, energy, industry, transportation, waste, agriculture, marine and fisher, water resources and health, in order to anticipate the impact of climate change up to 2030. Ministry of Finance has an important role in the ICCSR, to direct the fiscal policy to support renewable energy development including geothermal, to improve forest revenue, to access REDD carbon market, and to create incentive mechanism for sustainable forest management at the local level.